2017
DOI: 10.14507/epaa.25.2549
|View full text |Cite
|
Sign up to set email alerts
|

“We felt they took the heart out of the community”: Examining a community-based response to urban school closure

Abstract: Citation: Green, T. (2017). "We felt they took the heart out of the community": Examining a community-based response to urban school closure. Education Policy Analysis Archives, 25(21). http://dx.doi.org/10.14507/epaa.25.2549Abstract: Massive school closures are occurring in urban school districts across the United States. Research suggests that school closures are the outcome of racialized neoliberal policies and decades of disinvestment that have left many urban districts with fiscal deficits and declining s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 38 publications
(120 reference statements)
0
59
0
Order By: Relevance
“…School closures often position communities in a defensive role, requiring them to spell out the value of their individual school. It is telling that some of the studies of communities developing counternarratives to school closures mentioned above were focused on cases of resistance from individual school communities (Green, 2017;Johnson, 2012;Kirshner & Pozzoboni, 2011). By adopting a common set of counterframes, however, it became possible for communities across different wards to move beyond defending their own schools.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…School closures often position communities in a defensive role, requiring them to spell out the value of their individual school. It is telling that some of the studies of communities developing counternarratives to school closures mentioned above were focused on cases of resistance from individual school communities (Green, 2017;Johnson, 2012;Kirshner & Pozzoboni, 2011). By adopting a common set of counterframes, however, it became possible for communities across different wards to move beyond defending their own schools.…”
Section: Discussionmentioning
confidence: 99%
“…Research has also documented innovative alternatives to closures. Green (2017) documented the story of a school that was re-opened after drawing on support from strong local partnerships, suggesting such community-based innovations could pose a possible alternative to closures. Still, more dramatic examples diminish the apparent destiny of closure.…”
Section: Inevitabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…These strategies include conducting original research (Christens & Dolans, 2011;Magrath, 2015;McLaughlin, Scott, Dechenese, Hopkins, & Newman, 2009;Oakes, Renee, Rogers, & Lipton, 2008;Winton & Evans, 2016); consulting others' research (McDonald, 2013;Winton & Evans, 2016); engaging traditional and social media (McDonald, 2013;Ramey, 2013); and lobbying decision-makers (Opfer, Young, & Fusarelli, 2008). Some researchers demonstrate how successful advocates draw on their social networks and social capital to secure policy changes (e.g., Green, 2017;Grossman, 2012), while others examine how groups frame issues strategically (e.g., Feuerstein, 2015;Itkonen, 2009).…”
Section: What Do We Know About Educational Advocacy?mentioning
confidence: 99%
“…Unfortunately, evidence suggests that a majority of students affected by closures do not end up in schools that are better than their origin school due to the lack of higher performing local options (CREDO 2017). Moreover, studies in receiving schools have found that redistricted students felt stigmatized as “dumb” and “failures” in their new schools, potentially introducing a negative effect that extends beyond academic performance (Dill et al, 2016; Gordon et al, 2018; Green 2017; Kirshner et al, 2010).…”
Section: Introductionmentioning
confidence: 99%